Hubungan Antara Keintiman Keluarga Dengan Kejadian Premenstrual Syndrome Pada Kader Posyandu Usia Produktif Di Puskesmas Manisrenggo Klaten - Prasetya, Avip Rahmat, dr. Yusuf Alam Romadhon, M.Kes, dr. Listiana Masyita Dewi, M.Sc (2015)
Background: According to World Health Organization (WHO), premenstrual syndrome had higher prevalence in Asian countries than Western countries. Pelayanan Kesehatan Ramah Remaja (PKRR) mentioned that the main problems women in Indonesia is menstrual disorders. Family would be a factor that causing stress, besides interpersonal factor, behaviour factor, and biological factor. Divorce is one of the factor that cause depression in the family. Based on the background, the authors are interested want to raise the topic of research on the relationship between family intimacy and the PMS incidents in the Manisrenggo Public Health Center Klaten. Goal: The goal of the research was to find out the relationship between family intimacy and premenstrual syndrome incidents in productive age of posyandu cadres in the Manisrenggo public health center Klaten. Method: This research was analytic observasional by using cross sectional approach. The number of research respondents were 40. The sampling technique used purposive sampling. The level of intimacy was measured by Muchlas & Sudiyanto family intimacy questionnaire, while the premenstrual syndrome was measured by SPAF questionnaire. The data were analyzed by Spearman hypothesis test in SPSS 22 for Windows. Result: The research result showed that the p value = 0,002 (p < 0,05). r value = 0,447 showed that there was relationship between family intimacy and premenstrual syndrome incidents complience by moderate correlation. Conclusion: There is relationship between family intimacy and premenstrual syndrome incidents in productive age of posyandu cadres in the Manisrenggo public health center Klaten.